Sistem Seleksi Keputusan Kelayakan Penerima Bantuan Sosial Di Perumahan Griya Serpong Asri Menggunakan Metode Weight Product - Zain Fauzi, Irfan; Darmawan, Redi (CV. Shofanah Media Berkah, 2024)
Social Assistance (BANSOS) is a program from the government in handling the problems of underprivileged citizens in the form of money or goods that aim to help the poor or unable to afford to be vulnerable to social risks. In the implementation of Social Assistance, there is a phenomenon where residents are financially able but also receive assistance or not yet precisely the prospective recipients of social assistance, there is no system that can assist in the selection of potential recipients of Social Assistance. So far the election of residents is based on a calculation process that still uses calculations that have not been computerized so that the calculation process is not clear and whether it is correct or not is still doubtful. In this study, the WP (Weight Product) method will be used. The WP (WEIGHT PRODUCT) method is a method that uses multiplication to relate attribute ratings, where the rating of each attribute must be raised to the first power of the attribute's weight. The use of the Weight Product method in selecting beneficiaries of social assistance aims to provide clearer calculations, where previous selections seemed less reliable because the calculations have been computerized so that the calculations will be clearer and more transparent and there will be detailed reports to prove the correctness of the elections made. And the results of calculations from the application using the Weight Product (WP) method produce alternatives V4 from alternatives v1 to V10 with a value of 0,2395 as citizens who are eligible to receive Social Assistance.